The state of self-regulated learning and academic dishonesty of undergraduate students during online learning - Kusuma, Anggita Nurindah (Psychological Research and Intervention, 2022)
The purpose of this study was to determine the condition of academic problems in the form of self-regulated learning and academic dishonesty in students during online learning and to examine the effect of self-regulated learning on academic dishonesty. This type of research is a correlational of quantitative approach. The study was conducted on 410 students in Special Region of Yogyakarta using online self-regulated learning scale and academic dishonesty scale. The results of this study indicate that student's self-regulated learning is mostly in the medium category with percentage of 52%. The aspect of self-regulated learning that has the highest average score is environment structuring, while the lowest aspect is time management. For academic dishonesty, most students are in the moderate category with percentage of 45.6%. this study also shows the Fcount value of 24.471, a significance value of 0.00, and the regression equation Y=23,816-0.090 which means that self-regulated learning has a negative effect on academic dishonesty. Self-regulated learning contributes 5.7% to academic dishonesty while 94.3% is influenced by other factors.